Kajian Geometri Jalan Tambang untuk Meningkatkan Produksi Penambangan Andesit PT Mandiri Sejahtera Sentra (MSS), Desa Sukamulya, Kecamatan Tegalwaru, Kabupaten Purwakarta, Provinsi Jawa Barat - Nurhadi Widodo; Zaenal; Indra Karna (Bandung Conference Series: Mining Engineering, 2022)
Abstract. There are several things that affect production, including circulation time and work efficiency. For research conducted on the geometry of the mine road, it is based on AASHTO (American Association of State Highway and Transportation Officials) in 1993 and Ministerial Decree No. 1827/K/30/MEM/2018. The haul road geometry studies carried out include the actual width of the straight road, the width of the bend road, the slope of the road, the radius of the bend, the superelevation, and the actual rimpull which will be compared with the results of calculations based on the AASHTO theory. Based on this theory, the study of the geometry of the road is associated with the production of loading equipment and transportation equipment which can later increase the production of desiccated rock mining. From the results of production observations carried out starting from the hopper to the loading point, where when comparing the theoretical calculation results obtained for the straight condition road width between 3.8 m and 10.69 m, the condition of this road grade is quite varied between 0-32 %. For rimpull available on conveyances ranging from Gear-1 to Gear-8. Based on the results of calculations that have been carried out for the production of loading equipment of 122.96 BCM/hour and for transportation equipment of 121.8 BCM/hour. For this production, the production target of 130.4 BCM/hour is not sufficient. Improvement efforts to increase production of andesite stone mining are by widening roads that do not meet AASHTO standards and also reducing height differences on road slopes that do not meet the standards of Ministerial Decree No. 1827/K/30/MEM/2018 as well as maximizing the speed per road segment on the conveyance. After the repair process was carried out, the production from loading equipment was 138.4 BCM/hour and transportation equipment was 137.7 BCM/hour, which had met the production target of 130.4 BCM/hour. Abstrak. Pada penelitian ini difokuskan pada jalan angkut dalam rangka meningkatkan produksi penambangan. Terdapat beberapa hal yang mempengaruhi produksi, diantaranya waktu edar dan juga efisiensi kerja. Penelitian yang dilakukan terhadap geometri jalan tambang berpijak pada AASHTO (American Association of State Highway and Transportation Officials) tahun 1993 dan Kepmen No. 1827/K/30/MEM/2018. Kajian geometri jalan angkut yang dilakukan diantaranya meliputi lebar jalan lurus, lebar jalan tikungan, kemiringan jalan, jari-jari tikungan, superelevasi, dan rimpull secara aktual yang akan dibandingkan dengan hasil perhitungan berdasarkan teori AASHTO. Berdasarkan teori tersebut untuk kajian geometri jalan tersebut dikaitkan dengan produksi alat muat dan alat angkut yang nantinya dapat meningkatkan produksi penambangan batu andesit. Hasil pengamatan produksi yang dilakukan mulai dari hopper menuju loading point, dimana ketika membandingkan antara hasil perhitungan secara teoritis didapatkan untuk lebar jalan kondisi lurus diantara 3,8 m sampai 10,69 m, kondisi dari grade jalan ini pun cukup bervariasi antara 0 - 32%. Rimpull yang tersedia pada alat angkut mulai dari Gear-1 hingga Gear-8. Berdasarkan hasil perhitungan yang sudah dilakukan untuk produksi dari alat muat sebesar 122,96 BCM/Jam dan untuk alat angkut sebesar 121,8 BCM/Jam. Untuk produksi tersebut belum memadai target produksi sebesar 130,4 BCM/Jam. Upaya perbaikan untuk meningkatkan produksi penambangan batu andesit adalah dengan cara memperlebar jalan yang belum memenuhi standar AASHTO dan juga menurunkan beda tinggi pada kemiringan jalan yang tidak sesuai standar Kepmen No. 1827/K/30/MEM/2018 serta memaksimalkan kecepatan per segmen jalan pada alat angkut. Setelah dilakukan proses perbaikan didapatkan produksi dari alat muat sebesar 138,4 BCM/Jam dan alat angkut sebesar 137,7 BCM/jam, dimana sudah memenuhi target produksi sebesar 130,4 BCM/Jam.